An Analysis of Pradhan Mantri Fasal Bima Yojana (PMFBY): Expectations and Reality - Ghosh, Sumit (International Journal of Advanced Science and Technology, 2019)
Agriculture is a risky venture which is susceptible to various risks arising from weather variability, fluctuations in input and output price, difficulties in storage, pest attack and diseases. Although there are many risk mitigating tools, whenever there is a crop failure, crop insurance is considered to be the effective mechanism to compensate the farmers for their losses. One of the policy interventions in recent times to minimise the risk associated with agricultural production is the introduction of Pradhan Mantri Fasal Bima Yojana (PMFBY) in 2016. The previously implemented schemes because of their lower penetration and coverage met with limited success. To protect and double farmers’ income by 2022 is the major objective and a shift from increasing farm production to increasing farm income is the important policy change of this present scheme. But the scheme so far hasn’t had much success as coverage is far below the expected level. Using secondary data, the present paper is an attempt to examine the performance of the scheme.